Digital transformation in times of crisis: Challenges, attitudes, opportunities and lessons learned from students’ and faculty members’ perspectives - Aljanazrah, Ahmad; Yerousis, George; Hamed, Ghadeer; Khlaif, Zuheir N. (Frontiers in Education, 2022)
The COVID-19 crises forced and accelerated digital transformation in higher education institutions. Acceptance of the adoption of digital technologies in those institutions as well as their digital and educational readiness and resilience are important key success factors for this transformation. The objective of this study was to explore challenges, attitudes, opportunities and lessons learned of digital transformation in times of crises at the university level from faculty members’ and students’ perspectives. The study used Unified Theory of Acceptance and Use of Technology (UTAUT) as a theoretical framework. In order to achieve the objective of the study a qualitative method was used. A total of 14 focus group interviews with 62 faculty members and 37 students were conducted in a mid-size university in Palestine. Thematic analysis was used to analyze data gathered from the focus group sessions. Results revealed many challenges toward digital transformation including technical and pedagogical infrastructure, social conditions, ease of use of software, digital pedagogy and online assessment. There are positive attitudes towards the availability of online resources and digitizing theoretical courses. However, students and faculty members still feel that they are not prepared enough for online education and expressed negative attitudes when digitizing practical courses. In order to achieve effective online teaching and learning, good preparation is a must for both students and lecturers which is not followed in actual delivery. Results also revealed several opportunities and benefits of digital transformation, namely, flexibility and the opportunity to develop new technical and educational skills. Researchers recommend carrying out this study in other universities and within different social and cultural contexts and applying mixed approach methodology for validating emerged results.